Do Our Children Have a Chance? A Human Opportunity Report for Latin America and the Caribbean - Molinas Vega, José R.; Paes de Barros, Ricardo; Saavedra Chanduvi, Jaime; Giugale, Marcelo; Cord, Louise J.; Pessino, Carola; Hasan, Amer (World Bank, 2012)
This book reports on the status and evolution of human opportunity in Latin America and the Caribbean (LAC). It builds on the 2008 publication in several directions. First, it uses newly available data to expand the set of opportunities and personal circumstances under analysis. The data are representative of about 200 million children living in 19 countries over the last 15 years. Second, it compares human opportunity in LAC with that of developed countries, among them the United States and France, two very different models of social policy. This allows for illuminating exercises in benchmarking and extrapolation. Third, it looks at human opportunity within countries, across regions, states, and cities. This gives us a preliminary glimpse at the geographic dimension of equity, and at the role that different federal structures play. The overall message that emerges is one of cautious hope. LAC is making progress in opening the doors of development to all, but it still has a long way to go. At the current pace, it would take, on average, a generation for the region to achieve universal access to just the basic services that make for human opportunity. Seen from the viewpoint of equity, even our most successful nations lag far behind the developed world, and intracounty regional disparities are large and barely converging. Fortunately, there is much policy makers can do about it.